Correlation between Gender and Occupation with Severity of Stress, Depression, and Anxiety during the COVID-19 Pandemic - Apsari, Putu Indah Budi; ATWN, Anak Agung Sagung; Suryanditha, Putu Arya; Widhidewi, Ni Wayan; Wijaya, Made Indra (Muhammadiyah Medical Journal, 2024)
Background: Mental health was a severe problem among tourism workers during the COVID-19 pandemic. Purposes: This study aimed to determine the correlation of gender and occupation with the level of depression, anxiety, and stress during the COVID-19 pandemic. Methods: This research used a cross-sectional analytic study to recruit subjects grouped into tourism and non-tourism workers. This research took place in Bali province during the July-August 2023 period. Level of depression, anxiety, and stress score was assessed using Depression, Anxiety, Stress Score (DASS) questionnaires by the Google form sheet and analyzed by Chi-square test with SPSS version 27. Result: A total of 138 subjects consisting of 32 (23.2%) males and 106 (76.8%) females, 127 (92.0%) tourism workers, and 11 (8.0%) non-tourism workers. There was a positive correlation between occupation and level of depression, anxiety, and stress, while there was no significant correlation found in gender. Conclusion: Occupation in the tourism sector correlated with the severity of stress, depression, and anxiety during the COVID-19 pandemic.